Environmental Impact Assessment of Recycled Wastes on Surface and Ground Waters : Vol. 1: Concepts ; methodology and chemical analysis - . Kassim, Tarek A.; Williamson, Kenneth J (New York : Springer, 2005)
Annotation Volume 3: Engineering Modeling and Sustainability. This 3-volume reference presents the latest findings in impact assessment of recycled hazardous waste materials on surface and ground waters. Topics covered include chemodynamics, toxicology, modeling and information systems. The book serves as a practical guide for the monitoring, design, management, or conduct of environmental impact assessment. Each volume contains the table of contents of all volumes.
Includes bibliographical references and index.
Keywords: Groundwater